Patents and Economic Growth in Morocco: Empirical Evidence From ARDL Bounds Testing - Bouzggd, Mohamed; Elbourki, Mohamed; Arbia, Anass (International Journal of Economics and Financial Issues, 2025)
This study examines the short- and long-term relationship between innovation, measured by patent filings, and economic growth in Morocco over the period 2004–2023, using disaggregated quarterly data. After confirming the presence of mixed integration orders and a cointegration relationship using the bounds test, the ARDL model was estimated, supplemented by an error correction model (ECM) to analyse short-term dynamics. The empirical results reveal that, in the long term, patents have a positive and significant effect on GDP, while education and population growth have a negative impact; FDI and ERD are not decisive factors. In the short term, innovation and FDI support growth, while GFCF and immediate education have negative effects, offset by a favorable delayed effect of education. Empirical evidence suggests the need for integrated policies promoting innovation, matching training and employment, and managing demographic transition in order to support sustainable growth.